OPTIMIZATION OF THE ANP AND SET COVERING METHOD FOR THE ALLOCATION OF TANKER IN THE EAST SEA REGION OF INDONESIA - Ahmadi Ahmadi; Arica Dwi Susanto; Arys Susanto; Okol S Suharyo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2018)
As an archipelago which has a wider sea area than land, Indonesia, in this case the oil company, must be able to serve and accommodate oil throughout the Indonesian sea, especially the eastern region. The lack of tanker cause the run out of fuel oil in remote areas, so there needs to be a sector division included in oil companies. The method used by researchers was the Analytic Network Process (ANP) approach and the set covering problem method. By determining the right dock location for the Tanker, the dock would be able to cover the entire existing sector, and through the determination of the proper tanker assignment plan, the entire territory of Eastern Indonesia would be able to be covered by the presence of the Tanker. The results of the study show that the candidate starting point assignment was produced by 4 (four) ports as the starting point for the assignment of tankers. These ports consist of Ambon in charge of covering sectors 4, 5, 6 and 7, Makasar port was in charge of sector 1 and to cover sector 3 while Tegal port is in charge of covering the patrol sector 2